A new series of naphthyl-thiosemicarbazone and thio/carbohydrazone derivatives: Synthesis, spectroscopic elucidation, dual enzyme inhibition targeting carbonic anhydrase/ acetylcholinesterase and molecular docking studies - Yakan, Hasan; Muğlu, Halit; Erdoğan, Musa; Türkeş, Cüneyt; Demir, Yeliz (Elsevier BV, 2025)
New naphthyl-thiosemicarbazone derivatives (1–9) were obtained from 1-naphthaldehyde and numerous thiosemicarbazides. New naphthyl-thio/carbohydrazones (10–12) were prepared from 1-naphthaldehyde and various thio/carbohydrazides. FT-IR, 1H NMR, 13C NMR, and elemental analysis were used to elucidate the structures of the newly obtained compounds. The inhibitory effects of these compounds against human carbonic anhydrase isoforms I and II (hCA I and hCA II) and acetylcholinesterase (AChE) were systematically evaluated. Several compounds exhibited potent inhibition, particularly derivatives bearing halogenated and electron-donating aromatic substituents. Among them, compound 11 demonstrated the strongest inhibition for all three enzymes, with KI values of 52.42 nM (hCA I), 59.23 nM (hCA II), and 40.16 nM (AChE), surpassing the reference standards acetazolamide and tacrine. Structure–activity relationship (SAR) analysis highlighted the critical influence of substituent type and position on enzymatic activity. In addition, molecular docking simulations were conducted to elucidate the binding interactions of the most potent compound with hCA I, hCA II, and AChE enzymes. The docking results supported the in vitro findings, revealing favorable binding energies and key interactions such as π–π stacking and hydrogen bonding, especially for compound 11.